Enjoying Water in a Fragmented City: The Rhine–Herne Canal as a Mirror of a Changing Society - Eckardt, Frank (Journal of Public Governance, 2021)
Objectives: This article aims at increasing the knowledge on how cities are changing by processes of post-industrialism. Research Design & Methods: The article reviews the historical process of the use of water in the Rhine–Herne canal and the surrounding city of Gelsenkirchen. Findings: The article shows that the canal has regained significance to people. However, depending on the social status, the canal means something different now. For the urban poor, it is again a place for refreshment and free swimming. For the middle class, it is a popular spot for dining out and acquiring a sense of maritime atmosphere. Implications / Recommendations: Water in post-industrialism requires a socially differentiated understanding. Contribution / Value Added: The article contributes to a critical review on contemporary urban planning policies regarding water. Article classification: theoretical article (conceptual article) JEL classification: O29, Z13